2000
DOI: 10.1128/jb.182.21.6145-6153.2000
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection for Mutations Affecting Bioconversion of Aromatic Compounds in Agrobacterium tumefaciens : Analysis of Spontaneous Mutations in the Protocatechuate 3,4-Dioxygenase Gene

Abstract: A positive selection method for mutations affecting bioconversion of aromatic compounds was applied to a mutant strain of Agrobacterium tumefaciens A348. The nucleotide sequence of the A348 pcaHGB genes, which encode protocatechuate 3,4-dioxygenase (PcaHG) and ␤-carboxy-cis,cis-muconate cycloisomerase (PcaB) for the first two steps in catabolism of the diphenolic protocatechuate, was determined. An omega element was introduced into the pcaB gene of A348, creating strain ADO2077. In the presence of phenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The involvement of the pcaHGBCD and pcaIJF operons (Atu4538 to Atu4542 and Atu4547 to Atu4549) encoding proteins in C58 was previously shown by Parke (29). MH4F, methylene-tetrahydrofolate; H4F, methyl-tetrahydrofolate.…”
Section: Involvement Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of the pcaHGBCD and pcaIJF operons (Atu4538 to Atu4542 and Atu4547 to Atu4549) encoding proteins in C58 was previously shown by Parke (29). MH4F, methylene-tetrahydrofolate; H4F, methyl-tetrahydrofolate.…”
Section: Involvement Ofmentioning
confidence: 99%
“…strain HR199 (16) is presented below. ate 3-monooxygenase, PobA (Atu4544), is involved in the direct conversion of p-hydroxybenzoic acid from pCA into protocatechuic acid (29).…”
Section: Involvement Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, upon their exposure to an appropriate precursor, pcaB-blocked cells give rise to secondary mutants that are protected by their inability to generate the tricarboxylate compound. The application of a positiveselection procedure based on the toxic effect has resulted in the isolation of informative structure-function mutations in upstream enzymes and their regulators (7,14,26,27,34). However, this approach had met with limited success in the case of the initial steps of the hydroxycinnamate pathway because the numerically predominant secondary mutants were those blocked in steps towards the end of the catabolic sequence.…”
mentioning
confidence: 99%
“…ADP1 and Agrobacterium tumefaciens feed on protocatechuic acid and catabolize it to succinyl-CoA and acetyl-CoA, and that disruption of the pcaB gene, involved in a downstream step of the pathway, causes accumulation of an intermediate, -carboxy-cis,cis-muconic acid, which exerts growth inhibition in minimal medium containing succinate as a carbon source. 28,29) Our homology search of the B. subtilis genome showed that there is no homolog to the Acinetobacter sp. and A. tumefaciens pcaHG genes encoding protocatechuate 3,4-dioxygenase catalyzing the conversion of protocatechuic acid tocarboxy-cis,cis-muconic acid, which suggests that the protocatechuic-acid catabolic pathway of B. subtilis is different from those of Acinetobacter sp.…”
Section: Susceptibility To Flavonoidsmentioning
confidence: 99%